Freestall barn design and management for cow comfort - W.G. Bickert; John F. Smith (Kansas Agricultural Experiment Station Research Reports, 1998)
Proper design, construction, and care of freestalls are essential to cows using the stalls and realizing their potential benefits for comfort and health. Freestall dimensions depend upon particular designs and are compromises between ensuring optimum cleanliness and providing a spacious area for the ultimate in cow comfort. Freestalls designed to meet these fundamental needs will be most used. Most likely, no perfect freestall design exists. Rather, several freestall designs may satisfy the basic requirements of the cow perfectly well!; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Freestall; Cow comfort; Bedding